PENGEMBANGAN MODEL PARAMETRIK METODE DEA DALAM MENGUKUR TINGKAT EFISIENSI BIAYA PADA PERBANKAN SYARIAH DI KOTA SEMARANG - Willyanto Kartiko Kusumo; Abdul Karim (Universitas Semarang, 2017)
Efficiency is one of the performance parameters that are theoretically is one of the underlying performance of the overall performance of an organization. Efficiency in the banking sector is one of the performance parameters are quite popular, widely used because it is a response to the difficulties in calculating measures of bank performance. Measurement of the efficiency of banking can be done with the development of non-parametric statistical model by using Data Envelopment Analysis (DEA). In general, there are three approaches to the basic concepts of financial sector efficiency model that is cost efficiency, standard profit efficiency and alternative profit efficiency. In this research method used is the Data Envelopment Analysis (DEA). In this method, profit is modeled to deviate from its efficient frontier profit due to random noise and inefficiency. Profit in this method is affected by the function of input and output, while input and output used in this study is the Third Party Funds, Capital paid, placements with Bank Indonesia. By using this method the efficiency of Islamic banking DEA during 2012 to 2015 experienced an annual average efficiency of 94.37% and profit Islamic banking is heavily influenced by the financing facilities and placements with Bank Indonesia.